Promoting Web-based Education on Healthcare careers - Lockhart, Elizabeth (My University, 2023)
The Doctor of Nursing Practice project was formulated after the “Nurse Like Me” project began with middle and high school students to increase their interest in nursing. No website platform at ECU displayed healthcare professions such as nursing, occupational therapy, speech therapy, physical therapy, emergency medical technician, radiology technology, billing, coding, and other healthcare careers. This DNP project was created and implemented to increase interest in healthcare careers among middle and high school students. The project site champion formulated the idea of a website to be utilized in middle and high school for easy accessibility. The DNP student created a website that included personal videos from volunteers who had worked in these professions. The DNP project implementation started on September 27, 2022, to November 11, 2022, and included students who were in 7th grade to 12th grade only. The DNP project implementation only included students in North Carolina who visited the career and technical education webpage. The guidance counselors who helped the DNP student implement the project were in middle and high schools in central North Carolina. The surveys were located on each page and within all 35 web pages. The results revealed that 84% of middle and high school students found the website helpful and informative, and 52% were interested in nursing. This project supports using a healthcare website for middle and high school students to assist with career development.
Keywords: healthcare website, student, nursing, career development, education